2019
DOI: 10.17352/anpc.000035
|View full text |Cite
|
Sign up to set email alerts
|

The factors Related to Maternal-Fetal Attachment: Examining the Effect of Mindfulness, Stress and Symptoms during Pregnancy

Abstract: Background:The development of a successful relationship between a mother and her developing fetus to foster maternal behavior attainment. Diverse factors such as psychophysiological elements infl uence the maternal-fetal relationship. Mindfulness, a psychological process, increasingly apples to the research of pregnant women's wellbeing. However, most studies focus solely on physiological outcomes; few consider the maternal-fetal bonding.Purpose: This research aims to investigate whether factors of stress, sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…The author believes that no matter what the age of a pregnant woman, MIB is still present because it is an emotional tie between the mother and her baby. Furthermore, consistent with other studies, the current study revealed that there are no significant statistical differences in the mean level of MIB among gestational ages (Tsao et al, 2019;Zolfaghari et al, 2019). The author believes that as fetal growth occurs, pregnant women can feel the new movements of the baby, which makes the experience more physical for them and may lead them to interact more adequately with the fetus, thus increasing MIB.…”
Section: Discussionsupporting
confidence: 89%
“…The author believes that no matter what the age of a pregnant woman, MIB is still present because it is an emotional tie between the mother and her baby. Furthermore, consistent with other studies, the current study revealed that there are no significant statistical differences in the mean level of MIB among gestational ages (Tsao et al, 2019;Zolfaghari et al, 2019). The author believes that as fetal growth occurs, pregnant women can feel the new movements of the baby, which makes the experience more physical for them and may lead them to interact more adequately with the fetus, thus increasing MIB.…”
Section: Discussionsupporting
confidence: 89%